PENGAMANAN BERKAS DOKUMEN MENGGUNAKAN FUNGSI ALGORITMA STEGANOGRAFI LSB - Indra Gunawan; Sumarno Sumarno; Eka Irawan; Heru Satria Tambunan (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2018)
In the World of Information Technology computer science, data security something that is very important so that data can not be misused by some parties who have not / not have rights. In the delivery of documents documents is needed a security so that the document file can be accepted by those who have the right to receive it. It is therefore very necessary to process a document encryption / encryption file. Among the science of cryptography that can secure the document file such as LSB Steganography Algorithm (Least Significant Bit). This analysis aims to improve the security of document files by encoding a document file, then providing a password into the document file.Keywords : Encryption, Data Security, LSB Steganography, Files, Documents